2023
DOI: 10.3390/cancers15133282
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Gastrin-Releasing Peptide as a Biomarker in Lung Neuroendocrine Neoplasm

Abstract: There is a lack of effective biomarkers for diagnosing lung neuroendocrine neoplasms (LNENs). A known small cell lung cancer (SCLC) biomarker is a pro-gastrin-releasing peptide (ProGRP), but not for all LNENs, especially for bronchopulmonary carcinoids. This study aimed to evaluate the diagnostic value of ProGRP and chromogranin A (CgA) in diagnosing LNENs. The ProGRP and CgA levels in 290 cases of LNENs and 54 healthy controls (HCs) were measured. The median ProGRP concentration in the group of LNEN patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…ProGRP and NSE are diagnostic biomarkers of SCLC with various sensitivities ranging from 47 to 80% [ 21 , 32 , 33 , 34 ]. Furthermore, a recent study reported excellent sensitivity and specificity (94.8% and 100%, respectively) for ProGRP in lung neuroendocrine neoplasms [ 40 ]. ProGRP and NSE are mainly released by lung cancers, while CYFRA21-1 and NGAL are released by various solid cancers [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…ProGRP and NSE are diagnostic biomarkers of SCLC with various sensitivities ranging from 47 to 80% [ 21 , 32 , 33 , 34 ]. Furthermore, a recent study reported excellent sensitivity and specificity (94.8% and 100%, respectively) for ProGRP in lung neuroendocrine neoplasms [ 40 ]. ProGRP and NSE are mainly released by lung cancers, while CYFRA21-1 and NGAL are released by various solid cancers [ 34 ].…”
Section: Discussionmentioning
confidence: 99%